The Relationship Between Self Efficacy and StudentWorkReadiness in Vocational High Schools - Aslamiah Lubis; Khairani Khairani (Universitas Negeri Padang, 2021)
As a first step to enter the world of work, students are required to be able to develop their abilities, knowledge, skills and personality attributes as a provision for their readiness to work in order to be able to compete in getting the desired job. However, in fact there are still students who are not ready to enter the world of work, with there are also graduates who are not absorbed by the world of work. In connection with this, there are several factors that can affect job readiness, one of which is Self Efficacy. This study aims to determine the relationship between Self Efficacy and job readiness in vocational students. The method used in this research is descriptive and correlational. The study population was 418 grade XII students who had completed an internship at SMK Negeri 9 Padang, with a sample of 222 students, who were selected by simple random sampling technique. Collecting data using Self Efficacy questionnaires and work readiness with a Likert scale model. Data processing using Microsoft Excel. To see the relationship between the two variables using the Pearson correlation product moment.The results of this study indicate: (1) Self Efficacy is in the high category with a percentage of 58.1%, (2) job readiness is in the high category with a percentage of 59.9%, (3) there is a significant positive relationship between Self Efficacy and readiness. work with rxy = 0.415 and a significant level of 0.000. Based on the research results, there is a significant positive relationship between Self Efficacy and work readiness, meaning that the higher Self Efficacy, the higher work readiness and vice versa. Work readiness and self-efficacy of SMK Negeri 9 Padang students are high, but there are still a small number of students who don't have Self Efficacy and work readiness to enter work.